REDD Alert for developing countries? Are their forests in risk of internationalisation with the recent developments within the UN climate change regime? - Pardavé, Guillermo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
There is an increasing awareness of the role that forests play in the global carbon cycle and the negative impact that deforestation has on global warming. Deforestation accounts for nearly 17 percent of the total annual Greenhouse Gas (GHG) emissions. Forested developing countries, particularly those from South America and Africa, are the main contributors to that amount. This situation has boosted the perception that the new global climate change deal following the Kyoto Protocol commitments, ending in 2011, must include financial incentives to reward forested developing countries that succeed in reducing the rate of deforestation. Although discussed at the Kyoto Conference, payments for Reducing Emissions from Deforestation and Forest Degradation (REDD) were not included in the Protocol for a series of political and technical reasons. Currently the UN framework only allows reforestation and afforestation projects as part of the Clean Development Mechanism (CDM), herefore, only one part of the equation required to effectively tackle the problem of forest loss has been considered.
Keywords: Estudios internacionales; https://purl.org/pe-repo/ocde/ford#5.09.01